(untitled) (Scientific journal of the Fergana State University, 2023)
This article discusses the propaganda work carried out by the Soviet government in Uzbekistan to strengthen its power. When studying the topic of the article, a detailed analysis of the literature summarizes the facts. One of the main tools of the Soviet government was to reveal the aims of our propaganda campaigns. The effective methods of Soviet ideological propaganda have been studied and analyzed. Particular attention is paid to the widespread use in this propaganda work of exaggerated information about people recognized as geniuses of communist ideology.